2018
DOI: 10.1136/bjsports-2017-098733
|View full text |Cite
|
Sign up to set email alerts
|

Objectively measured physical activity, sedentary behaviour and all-cause mortality in older men: does volume of activity matter more than pattern of accumulation?

Abstract: Objectives To understand how device-measured sedentary behaviour and physical activity are related to all-cause mortality in older men, an age group with high levels of inactivity and sedentary behaviour. Methods Prospective population-based cohort study of men recruited from 24 UK General Practices in 1978 -1980 . In 2010 surviving men were invited to a follow-up, 1655 (aged 71-92 years) agreed. Nurses measured height and weight, men completed health and demographic questionnaires and wore an ActiGraph GT3x a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
243
4
6

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 195 publications
(281 citation statements)
references
References 35 publications
(47 reference statements)
16
243
4
6
Order By: Relevance
“…Their results indicate that total MVPA with no bout requirement, MVPA in 5‐minute bouts, and MVPA in 10‐minute bouts resulted in similar risk reductions for all‐cause mortality. These data are similar to a recent report on health outcomes in older men that found total activity, including light intensity and activity expressed in bouts, was inversely related to all‐cause mortality …”
Section: Introductionsupporting
confidence: 90%
See 1 more Smart Citation
“…Their results indicate that total MVPA with no bout requirement, MVPA in 5‐minute bouts, and MVPA in 10‐minute bouts resulted in similar risk reductions for all‐cause mortality. These data are similar to a recent report on health outcomes in older men that found total activity, including light intensity and activity expressed in bouts, was inversely related to all‐cause mortality …”
Section: Introductionsupporting
confidence: 90%
“…that found total activity, including light intensity and activity expressed in bouts, was inversely related to all-cause mortality. 7 In the research reported by Saint-Maurice and colleagues, the adjusted hazard ratios for all-cause mortality for increasing quartiles of total MVPA were 0.43, 0.24, and 0.27 for quartiles 2, 3 and 4, respectively (quartile 1 as reference). 6 In prior systematic reviews or meta-analysis using self-report PA data, the hazard or risk ratios for all-cause mortality when comparing the more or most active with the least active have been closer to 0.60 to 0.65.…”
mentioning
confidence: 94%
“…Of these, 1010 articles were excluded after title and abstract screening and 23 full-text articles were assessed for potential eligibility. 10,11,[19][20][21][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46] Of these 23 articles, six studies met the criteria. 10,11,[19][20][21]33 From the remaining 17 studies contacted via email, five of them provided the requested results.…”
Section: Study Selectionmentioning
confidence: 99%
“…10,11,[19][20][21][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46] Of these 23 articles, six studies met the criteria. 10,11,[19][20][21]33 From the remaining 17 studies contacted via email, five of them provided the requested results. [29][30][31][32]34 Eight studies did not provide cutoff point of LPA because data re-analysis was not available, [36][37][38][40][41][42]44,45 one study included participants with chronic kidney disease, 35 and the other three studies did not adjust for MVPA.…”
Section: Study Selectionmentioning
confidence: 99%
“…Clocking up just a few minutes at a time of any level of physical activity, rather than the recommended 10 minute bouts, is linked to a lower risk of death in older men as long as they reach the target of 150 minutes a week, suggested a study published in the British Journal of Sports Medicine 3. Each additional 30 minutes a day of light activity, such as gentle gardening or taking the dog for a walk, was associated with a 17% lower risk of death.…”
Section: Research Newsmentioning
confidence: 99%